Are sustainable tourists a higher spending market?. (June 2016) - Nickerson, Norma Polovitz; Jorgenson, Jake; Boley, B. Bynum
Abstract: Resistance to sustainability practices often stems from the industry's view that sustainable tourism requires a profitability tradeoff where the additional costs associated with sustainability do not pay off in increased economic returns, yet few studies have been attempted to prove or disprove this viewpoint. This study analyzed spending patterns and length of stay of visitors to Montana, USA to determine if strong geotravelers (higher sustainable behaviors) were different than those with less sustainable behaviors. Results found that total trip spending by strong geotravelers (US $1164) was significantly higher than the overall spending of both moderate (US $866) and minimal geotravelers (US $668). These findings suggest that sustainable travelers are a travel market to be reckoned with in the tourism marketing and business world. The combination of their pro-sustainable behavior and increased spending provides evidence of a market segment in which destinations can benefit. Highlights: Sustainable tourists (high geotraveler tendencies) spend more money than other visitors. Sustainable tourists spend more time in the destination. Sustainable travelers contribute beneficially to the triple bottom line of tourism businesses.